The Development of a DISPERSIA Code Program-Air Dispersion Program for Radiological Dose Assessment of Nuclear Facilities - Ryanto, Theo Alvin; Pane, Jupiter Sitorus; Setiawan, Muhammad Budi; Susilo, Yarianto Sugeng Budi; Husnayani, Ihda; Purwaningsih, Anik (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
The DISPERSIA-BRIN program, along with its sub-programs STDISPERSIA and WRDISPERSIA, was developed to enable swift and effective radiological analysis, essential for rapid decision-making during nuclear accidents. These programs were validated against SIMPACT version 1.0, confirming their accuracy and reliability. Python was selected as the primary programming language due to its simplicity and versatility. DISPERSIA-BRIN incorporates geospatial analysis tools, allowing researchers to visualize the radioactive material concentration and the dose impact on polar grids surrounding the nuclear facility. The program models the dispersion of concentrations and their dose effects, assessing their interaction with humans, livestock, and plants. This helps to identify high-dose areas, vulnerable populations, and emergency planning zones. A case study involving a hypothetical Nuclear Power Plant site demonstrated DISPERSIA-BRIN's capability to accurately calculate and visualize radionuclide dispersion, aiding in the identification of high-radiation areas.